2017
DOI: 10.1177/0267658317723684
|View full text |Cite
|
Sign up to set email alerts
|

Lexicalized structural priming in second language online sentence comprehension

Abstract: Prior work has shown intriguing differences between first language (L1) and second language (L2) comprehension priming of relative clauses. We investigated English reduced relative clause priming in Chinese adult learners of English. Participants of different education levels read sentences in a self-paced, moving window paradigm. Critical sentences had a temporarily ambiguous reduced relative clause. Across lists, critical sentences were rotated, so that they occurred either as prime or as target, and had eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 35 publications
(108 reference statements)
2
29
0
Order By: Relevance
“…The extent to which priming is lexically mediated in L2 processing is however debated. Some studies have shown lexically independent structural priming during comprehension (e.g., Nitschke et al, 2014;Wei et al, 2019), while others suggest lexically mediated structural priming (e.g., Wei et al, 2018). Thus, as also found in L1 studies of priming during comprehension discussed above, priming during comprehension in L2 speakers appears stronger in the presence of lexical overlap.…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…The extent to which priming is lexically mediated in L2 processing is however debated. Some studies have shown lexically independent structural priming during comprehension (e.g., Nitschke et al, 2014;Wei et al, 2019), while others suggest lexically mediated structural priming (e.g., Wei et al, 2018). Thus, as also found in L1 studies of priming during comprehension discussed above, priming during comprehension in L2 speakers appears stronger in the presence of lexical overlap.…”
mentioning
confidence: 58%
“…Furthermore, priming was found only in lexical overlap conditions (see also Wei et al, 2018), which suggests that priming during comprehension in L2 processing is strongly lexically mediated. Note that we did not find evidence that priming in the L2 is significantly more or less lexically mediated than in L1 processing.…”
Section: Reanalysis In L2 Processingmentioning
confidence: 91%
See 3 more Smart Citations